2016
DOI: 10.3389/fimmu.2016.00625
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of an In-depth Study of Immunoglobulin Gene Rearrangements When Ascertaining the Clonal Relationship between Concomitant Chronic Lymphocytic Leukemia and Multiple Myeloma

Abstract: Chronic lymphocytic leukemia (CLL) and multiple myeloma (MM) are hematological disorders that occur at different stages of B-cell development. It has been shown that CLL B-cells can differentiate into plasma cells in vitro and in vivo. CLL is the most frequent adult leukemia in the western world. It is a heterogeneous disease, characterized by clonal proliferation and the accumulation of mature CD5+ B lymphocytes (1). MM is a clonal plasma cell malignancy that accounts for more than 10% of all hematologic canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…MM is a disease related to a hematological disorder that appears at various stages of β-cells, and it accounts for 1% of all cancers, as well as 10% of hematological malignancies [32,33]. Based on recent studies, miRs have been identified as tumor-suppressor genes and play important roles in tumor pathogenesis [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…MM is a disease related to a hematological disorder that appears at various stages of β-cells, and it accounts for 1% of all cancers, as well as 10% of hematological malignancies [32,33]. Based on recent studies, miRs have been identified as tumor-suppressor genes and play important roles in tumor pathogenesis [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that serum Ig is produced by PCs differentiated from leukemic cells ( 23 ). Concomitant PC malignancies and CLL have been reported in several studies ( 231 , 232 ). Several studies showed that differentiation of CLL cells into ASPCs can occur spontaneously in vivo ( 23 , 24 ).…”
Section: What Can the Functional Features Of Cll B-cells Tell Us Aboumentioning
confidence: 95%
“…However, a common clonal origin is not a consistent finding, with many cases reporting a biclonal origin (6,8,10,12,34). It is noteworthy that discrepant results can be obtained for the same patient by phenotypic (i.e., with expression of different light chains and immunoglobulin isotypes) and molecular findings, supporting the need for clarifying the most accurate approach for clonality assessment (3,6,33,35). It is noteworthy that discrepant results can be obtained for the same patient by phenotypic (i.e., with expression of different light chains and immunoglobulin isotypes) and molecular findings, supporting the need for clarifying the most accurate approach for clonality assessment (3,6,33,35).…”
Section: Discussionmentioning
confidence: 99%
“…This lack of concordance could originate from heterogeneity of cases as well as from the use of divergent methods, such as immunophenotypic, cytogenetic and molecular studies. It is noteworthy that discrepant results can be obtained for the same patient by phenotypic (i.e., with expression of different light chains and immunoglobulin isotypes) and molecular findings, supporting the need for clarifying the most accurate approach for clonality assessment (3,6,33,35).…”
Section: Discussionmentioning
confidence: 99%